ÁJINIYAZ ShÍǴARMALARÍNDA ÚY BUYÍMLARÍ ATAMALARÍNÍŃ QOLLANÍLÍWÍ - Qarlıbaeva, G.E.; Sadıkova, R.S. (SCIENCE and SOCIETY, 2019)
The article discusses the names of household items. The study of the names of objects used at different historical periods in the life of the Karakalpak people from a linguistic point of view contributes to a deep study of the vocabulary of the Karakalpak language and receiving rich information about the history and ethnography of the people.
Keywords: vocabulary; semantics; style; dialect; historicism; ethnographism; phraseological units; phraseologism; literary language; linguistic culturology